Obstacles to Achieving the Principle of Accommodating Individual Differences among Students by Teachers from Their Perspective "A field study in cycle 1 schools in Lattakia city" - غانم, ثناء; شرّوف, أنساب; حسن, نسرين (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study aimed to knowing the obstacles to achieving the principle of accommodating individual differences among students by teachers from their perspective, and whether this differs according to different variables (academic qualification, experience in teaching, school type and the level of the class). To achieve the objectives of this study, a questionnaire for teachers of the schools of Lattakia city was made. This questionnaire included (42) items in dimensions (obstacles related to school environment, obstacles related to teaching process and obstacles related to teacher). It was applied on a random sample consisted of (178) teachers. The descriptive methodology has been followed. The results of the study from the perspective of teachers showed that most obstacles hinder teacher from achieving the principle of accommodating individual differences among students are the obstacles related to teachers, followed by the obstacles related to teaching process, then the obstacles related to school environment, mainly the high amount of educational and instructional responsibilities needed to be fulfilled in such limited time. Results showed that there are no difference in teachers' viewpoints according to the variables: academic qualification, teaching experience and the level of the class. It showed a difference in teachers' viewpoints according to school type in favor of state schools.